From regeneration to osteoarthritis in the knee joint: The role shift of cartilage-derived progenitor cells - Liu, Wenguang; Feng, Meng; Xu, Peng (Frontiers in Cell and Developmental Biology, 2022)
A mount of growing evidence has proven that cartilage-derived progenitor cells (CPCs) harbor strong proliferation, migration, and multiple differentiation potentials over the past two decades. CPCs in the stage of immature tissue play an important role in cartilage development process and injured cartilage repair in the young and active people. However, during maturation and aging, cartilage defects cannot be completely repaired by CPCs in vivo. Recently, tissue engineering has revealed that repaired cartilage defects with sufficient stem cell resources under good condition and bioactive scaffolds in vitro and in vivo. Chronic inflammation in the knee joint limit the proliferation and chondrogenesis abilities of CPCs, which further hampered cartilage healing and regeneration. Neocartilage formation was observed in the varus deformity of osteoarthritis (OA) patients treated with off-loading technologies, which raises the possibility that organisms could rebuild cartilage structures spontaneously. In addition, nutrition metabolism dysregulation, including glucose and free fatty acid dysregulation, could influence both chondrogenesis and cartilage formation. There are a few reviews about the advantages of CPCs for cartilage repair, but few focused on the reasons why CPCs could not repair the cartilage as they do in immature status. A wide spectrum of CPCs was generated by different techniques and exhibited substaintial differences. We recently reported that CPCs maybe are as internal inflammation sources during cartilage inflammaging. In this review, we further streamlined the changes of CPCs from immature development to maturation and from healthy status to OA advancement. The key words including “cartilage derived stem cells”, “cartilage progenitor cells”, “chondroprogenitor cells”, “chondroprogenitors” were set for latest literature searching in PubMed and Web of Science. The articles were then screened through titles, abstracts, and the full texts in sequence. The internal environment including long-term inflammation, extended mechanical loading, and nutritional elements intake and external deleterious factors were summarized. Last, the related mouse models used in CPC investigation were listed. Taken together, these results provide a comprehensive understanding of the underlying mechanism of CPC proliferation and differentiation during development, maturation, aging, injury, and cartilage regeneration in vivo.